Pembimbingan Kepribadian Dan Kemandirian Klien Pemasyarakatan Di Bapas Klas II Bengkulu - Lorita, Evi; Saputra, Harius Eko; Maryaningsih, Maryaningsih; C. Kader, Bando Amin; Dahlia, Dahlia; Nova, Nova (Universitas Dehasen Bengkulu, 2025)
Community service means directly institutionalising the practice of science, technology, arts and culture in society through scientific methods such as the socialisation of the three dharmas of higher education and noble responsibilities in an effort to develop community skills in carrying them out. This community service activity was carried out at the Balai Pemasyarakatan (Bapas Kelas II Bengkulu), which carried out its activities at the BAPAS Klas II Bengkulu Halfway House Jl. Lintas Bengkulu-Kepahiang Desa Taba Pasemah Kec. Talang Empat Kab. Bengkulu Tengah. The target of this activity is Correctional Clients in Bapas Class II Bengkulu. This activity is carried out with the aim of providing Personality Guidance and Independence of Correctional Clients at BAPAS Class II Bengkulu. The benefits of the implementation of community service carried out by lecturers and students of the Public Administration Study Program for Correctional Clients at BAPAS Class II Bengkulu are to create correctional clients who are independent and have noble personalities, and can consciously realise the mistakes that have been made and promise with their own personality not to repeat the mistakes that have been made.